Toluene and methylethylketone: effect of combined exposure on their metabolism in rat. (3rd July 2018) - Cosnier, Frédéric; Nunge, Hervé; Bonfanti, Élodie; Grossmann, Stéphane; Lambert-Xollin, Anne-Marie; Muller, Samuel; Sébillaud, Sylvie; Thomas, Aurélie; Gaté, Laurent; Campo, Pierre
Abstract: 1. Multiple exposures are ubiquitous in industrial environments. In this article, we highlight the risks faced by workers and complete the data available on the metabolic impact of a common mixture: toluene (TOL) and methylethylketone (MEK). 2. Rats were exposed by inhalation under controlled conditions either to each solvent individually, or to mixtures of the two. How the interaction between the two solvents affected their fate in the blood and brain, their main relevant urinary metabolites (o-cresol, benzylmercapturic acid for TOL and 2, 3-butanediols for MEK) and their hepatic metabolism were investigated. 3. Although the cytochrome P450 concentration was unchanged, and the activities of CYP1A2 and CYP2E1 isoforms were not additively or synergistically induced by co-exposure, TOL metabolism was inhibited by the presence of MEK (and vice versa). Depending on the relative proportions of each compound in the mixture, this sometimes resulted in a large increase in blood and brain concentrations. Apart from extreme cases (unbalanced mixtures), the amount of o-cresol and benzylmercapturic acid (and to a lesser extent 2, 3-butanediols) excreted were proportional to the blood solvent concentrations. 4. In a co-exposure context, ortho-cresol and benzylmercapturic acid can be used as urinary biomarkers in biomonitoring for employees to relatively accurately assess TOL exposure.